Formulation of Peel-off Gel Face Mask from Pandanus amaryllifolius (Roxb.) Leaves Extract - Tubagus Akmal; Yenni P. Tanjung; Sofa P. Nurlaela (Indonesian Journal of Pharmaceutical Science and Technology, 2022)
UV exposure is the most significant environmental risk factor that can be altered for skin cancer andmany other skin conditions. An antioxidant is a compound that can protect the skin from sun radiation.Pandanus amaryllifolius is a plant that has antioxidant activity because it contains polyphenols. Theobjective of this study is to formulate a pandan Wangi leaf extract peel-off gel facial mask and analyzehow variations in the extract's concentration affect the physical and chemical evaluation. In this study,three formulas were made with varying concentrations of extract, namely F1 (1%), F2 (3%), and F3(5%). The preparation was evaluated for 28 days at a controlled room temperature (180C-300C+20C).The evaluation carried out included a physical evaluation (organoleptic, spreadability, homogeneity,viscosity, dry time) and a chemical evaluation (pH). The results showed that F1, F2, and F3 met therequirements for physical and chemical evaluation. Variations in the concentration of Pandan Wangileaf extract had a significant effect (p<0.05) on the results of the preparation evaluation which includedorganoleptic, spreadability, and viscosity. While for the evaluation of homogeneity, dry time, and pHdid not show significant results (p> 0.05). These results indicate that pandanus leaf extract (Pandanusamaryllifolius Roxb.) can be formulated into a peel-off gel facial mask.